Teaching Anti-Corruption from an Early Age: An Analysis of Values in the Film Si Kumbi for Early Childhood Education - Dewanty, Salsabila; Masykuroh, Khusniyati (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study analyzed the anti-corruption values ​​depicted in the film series Si Kumbi published by the Corruption Eradication Commission (KPK) and its relevance to early childhood education. The film has proven to be effective in conveying various anti-corruption values, including honesty, responsibility, caring, justice, simplicity, hard work, discipline, courage, and accountability. These values ​​are demonstrated through the actions of the characters, who serve as positive role models for young viewers. However, the value of independence is not explicitly highlighted in the film, indicating an opportunity for further development in future narratives. This study highlights the importance of these values ​​in shaping children's moral and character development, particularly in fostering positive social behaviors such as honesty and responsibility. Based on the analysis, The series of Si Kumbi has proven to be an effective tool in introducing these values ​​to young viewers, although it would be better if it incorporated the dimension of independence to provide a more comprehensive approach to anti-corruption education. The findings highlight the potential of film as a resource for early childhood character education, helping to instill important values ​​for a better and more ethical future.